Spin and orbital magnetic moments of UTe2 induced by the external magnetic field - Alexander B. Shick; Urszula D. Wdowik; Itzhak Halevy; Dominik Legut (Scientific Reports, 2024)
Abstract Correlated band theory implemented as a combination of the relativistic density functional theory with exact diagonalization [DFT+U(ED)] of the Anderson impurity term with Coulomb repulsion U in the 5f shell is applied to the magnetic field polarized state of $$\hbox {UTe}_2$$ . We demonstrate that the DFT+U(ED) approach provides a good agreement with very recent x-ray absorbtion near edge structure (XANES) and x-ray magnetic circular dichroism (XMCD) experiments. The branching ratio for the $$M_{4,5}$$ edge transitions of uranium, and the valence spin-orbit interaction per hole were evaluated in a perfect agreement with the XANES. The orbital-to-spin moment ratio is calculated with DFT+U(ED) within the range of values extracted from XMCD data. The uranium atom 5f-shell ground state with 33 $$%$$ of $$f^2$$ and 58 $$%$$ of $$f^3$$ configurations is determined. Both XMCD and DFT+U(ED) point out the intermediate valence of uranium as well as itinerant-localized dichotomy in $$\hbox {UTe}_2$$ .